STUDI PENGUKURAN WAKTU KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN - Demmanggasa, Yultan (JNSTA ADPERTISI JOURNAL, 2023)
The purpose of measuring working time is to determine a duration required by the qualifying job by using standard method and working on standard level for carrying out the certain duty. Working time has a relevance of determining the level of worker’s achievement. Therefore, the application of work measurement is really needed to obtain a working time in order to produce a unit of goods. The results achieved shows that the employers work without considering the usage of standard time for carrying out the duties look like a robot. They work fast because of work demands. Consequently They give the bad work management.